Structural Characterization of AgI-AgPO3-Ag2WO4 Superionic Conducting Glasses by Advanced Solid-State NMR Techniques - Blais-Roberge, Mickaël; Santagneli, Silvia H. [UNESP]; Messaddeq, Sandra H.; Rioux, Maxime; Ledemi, Yannick; Eckert, Hellmut; Messaddeq, Younès [UNESP] (American Chemical Society (ACS), 2017)
Glass samples of composition 40AgI-(60-x)AgPO3-xAg2WO4 (0 ≤ x ≤ 25 mol %) have been prepared by the conventional melt-quenching method. These glasses receive renewed interest due to their ionic conductivity and transparency in the visible range. Because the physical and optical properties of these glasses are highly dependent on composition in this system, a comprehensive structural study has been carried out using Raman spectroscopy and 1D and 2D NMR of the 31P and 109Ag nuclei. With increasing Ag2WO4 content, the network is modified from a 1D Q(2)-like chain structure to a topology in which Q(1) and Q(0) species linked to octahedrally coordinated tungsten species dominate. This structural transformation increases the glass rigidity and stability against hydrolysis reactions. The compositional evolution of the phosphate speciation (in terms of Q(n)mW units) is consistent with maximum tungstate dispersion in glasses with x ≤ 10, while for glasses with higher tungstate content the data are more consistent with a random distribution of P-O-P, P-O-W, and W-O-W linkages. The 109Ag NMR chemical shifts are independent of composition and suggest that mobile silver ions are situated within cluster regions, furnishing a constant mixed iodide/oxide local environment.